Histórias Bíblicas e a formação literária infantil: contributos das narrativas bíblicas à leitura literária da criança na escola - Alcântara, Daphine Oliveira (Brasil, 2023)
The research is based on reflections about children's literary books that make up the collections of Early Childhood Education schools in Parintins (AM), the appreciation of biblical stories supported by the freedom of religious expressions and the possibility of inserting these narratives and knowledge in the child's reading formation . The reading of literary stories should constitute the school's actions, so our focus is to address the literary narratives contained in the most read and widely disseminated book - the Holy Bible. The richness of historical details and contexts, conquests, stories of heroes, kings, princesses and all the teachings of Jesus that the Bible has, is configured as rich literary material that can also constitute the reading routines in the formation of the little reader in school , in addition to the family sphere and religious institutions. The main objective was to investigate the contribution of biblical stories in the literary formation of the little reader, through a Field Research in 05 (five) Early Childhood Education Centers in Parintins, Amazonas, with the participation of 10 (ten) teachers who contributed to the development of the study. The techniques that made it possible to achieve the objectives were observation, interviews and reading circles with the children. Thus, carrying out this study on the literary potential of biblical stories brought to the academic space a relevant theme of appreciation and visibility of biblical literature. Researching biblical stories, as an alternative to be included in the literary repertoire of the little reader at school, provided experiencing dialogues and unique forms of expression, because in this biblical universe, it is possible to learn and share lessons for the current context in the process of human formation of children.